PENGARUH LATIHAN CLOSE KINETIC CHAIN EXERCISE TERHADAP PENURUNAN INTENSITAS NYERI DAN PENINGKATAN KEMAMPUAN FUNGSIONAL PADA OSTEOARTHRITIS LUTUT - Atik Swandari; Khabib Abdullah; Anastasia Putu Martha Anggarani; Adiya Rindi Krisnaudi (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2026)
Knee osteoarthritis (OA) is a degenerative musculoskeletal disease that commonly causes pain and decreased functional ability in older adults. This condition affects daily activities such as walking, prolonged standing, and climbing stairs. One of the physiotherapy interventions that can be applied is Close Kinetic Chain Exercise (CKCE), which aims to improve joint stability, muscle strength, and functional ability. This study aimed to analyze the effect of Close Kinetic Chain Exercise on reducing pain intensity and improving functional ability in patients with knee osteoarthritis. This study used a field experimental method with a one group pre-test and post-test design. The sample consisted of 11 female respondents aged 50–60 years diagnosed with knee osteoarthritis selected using purposive sampling. Pain intensity was measured using the Visual Analog Scale (VAS), while functional ability was assessed using the Jette Scale. Data were analyzed using the Wilcoxon Signed Ranks Test. The results showed that all respondents experienced decreased pain intensity and improved functional ability after the intervention. Statistical analysis showed a significance value of 0.003 (p < 0.05) for both pain and functional ability variables. It can be concluded that Close Kinetic Chain Exercise has a significant effect on reducing pain intensity and improving functional ability in patients with knee osteoarthritis